Bibliographie der Elateridenlarven-Literatur der Welt (1968-1972). - Gaedike, Reinhard (Contributions to Entomology = Beiträge zur Entomologie, 1975)
The present bibliography continues the paper published in 1969. All relevant publications from 1968 to 1972 are listed and annotated. The arrangement of the indexes of subjects and species corresponds to that of the first part.